Traditional Medicinal Ranunculaceae Species from Romania and Their In Vitro Antioxidant, Antiproliferative, and Antiparasitic Potential - Heller, Cristina D; Zahedifard, Farnaz; Doskocil, Ivo; Pamfil, Doru; Zoltner, Martin; Kokoska, Ladislav; Rondevaldova, Johana (International journal of molecular sciences, 2024)
Several Ranunculaceae species are used in folk medicine to eliminate pathologies associated with oxidative stress as well as parasitic infections; however, a number of studies confirming their pharmacological properties is limited. In this study, 19 ethanolic extracts obtained from 16 Ranunculaceae species were assayed for in vitro antioxidant, antiproliferative, and antiparasitic potential. The maximum antioxidant potential in both oxygen radical absorbance capacity (ORAC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays was observed for Aconitum toxicum extract [half-maximal inhibitory concentration (IC50) 18.7 and 92.6 μg/mL]. Likewise, Anemone transsilvanica extract exerted the most promising antiproliferative activity against Caco-2 (IC50 46.9 μg/mL) and HT29 (IC50 70.2 μg/mL) cell lines in 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Additionally, a dual antioxidant and cytotoxicity effect was demonstrated for Aconitum moldavicum and Caltha palustris extracts. Whilst the efficacy of extracts was modest against Trypanosoma brucei (IC50 ranging from 88.8 to 269.3 µg/mL), several extracts exhibited high potency against Leishmania infantum promastigotes (Aconitum vulparia IC50 18.8 µg/mL). We also tested them against the clinically relevant intracellular stage and found extract of A. vulparia to be the most effective (IC50 29.0 ± 1.1 µg/mL). All tested extracts showed no or low toxicity against FHs 74Int normal cell line (IC50 ranging from 152.9 to >512 µg/mL). In conclusion, we suggest the above-mentioned plant extracts as potential candidates for development of novel plant-based antioxidant and/or antiproliferative and/or antileishmanial compounds.
Keywords: Caco-2 Cells; buttercup family; léčivé rostliny; Rumunsko; Antioxidants; Caco-2 buňky; HT29 Cells; antioxidants; Cell Proliferation; rostlinné extrakty; tradiční lékařství; Plants, Medicinal; medicinal plants; antitrypanosomal; cytotoxicity; antioxidancia; antileishmanial; Romania; Ranunculaceae; antiparazitární látky; Humans; Medicine, Traditional; Antiparasitic Agents; proliferace buněk; Plant Extracts; plant extract; buňky HT-29; lidé